IMPROVING STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION THROUGH METACOGNITION METHOD - Meisalina Lourensia Tarigan and Rahmah (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2012)
The study aims at improving students’ achievement in reading comprehension applying Metacognition Method by conducting classroom action research. The population of this research twelfth grade students of SMP Negeri 41 Medan. The number of the students was 33 students. There were two kinds of data collected during the study, qualitative and quantitative data. The instrument for collecting the quantitative data was objective test of reading comprehension, while the instruments for qualitative data were gathered through interview, diary notes, and observation sheet. The qualitative showed that the students were interested in Metacognition Method. Based on the data analysis, the mean of the students score for orientation test was 52, 12 and for test in cycle I was 63, 63 and for test in cycle II was 76, 51. The conclusion is that Metacognition Method can improve the students’ achievement in reading comprehension. Keywords : Reading, Comprehension, Metacognition Method